Calcium Phosphate based Perforation Repair Materials using Human Gingival Fibroblasts: An in vitro Cytotoxicity Evaluation - Khashaba, Rania M. (New Horizons in Medicine and Medical Research Vol. 9, 2022)
New calcium phosphate cements (CPCs) with promising physical qualities for dental applications such as perforation repairs have been developed. However, there is a lack of evidence about the biological features of these novel materials, particularly in long-term scenarios. In a four-week in vitro cytotoxicity test, we examined the biological characteristics of three different types of CPCs. To obtain Types I, II, and III CPCs, a calcium phosphate paste containing 60% tetracalcium phosphate, 30% dicalcium phosphate dihydrate, and 10% tricalcium phosphate was combined with one of three aqueous solutions of citric acid, lactic acid, and malic acid. The specimens were placed in contact with human gingival fibroblast (HGF) grown cells for cytotoxicity testing, and cell mitochondrial function was measured using the MTT assay at four time points (24h, 1wk, 2wk, 3wk, 4wk). By four weeks, Type I had reached statistical parity with the Teflon control in terms of mitochondrial activity. By the third week, Type II had become indistinguishable from the Teflon Control, which was followed by a relapse. Type III was initially hazardous, but over the course of four weeks, it improved dramatically (P< 0.05) by >87 percent when compared to the Teflon control. Over the course of the four-week study, calcuim hydroxide (Life) was cytotoxic. For endodontic applications, Type I and Type III have appropriate biologic characteristics. The use of CPCs may thus improve the prognosis of teeth with furcation holes dramatically.